2020
DOI: 10.1002/jsfa.10261
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac protection of functional chicken‐liver hydrolysates on the high‐fat diet induced cardio‐renal damages via sustaining autophagy homeostasis

Abstract: BACKGROUND Cardio‐renal syndrome (CRS) is an integrative problem related to chronic malnutrition, obesity, etc. Amino acids and peptides are regarded as protective and essential for tissues. Pepsin‐digested chicken liver hydrolysates (CLHs), which are made from the byproducts of the poultry industry, are amino‐acid based and of animal origin, and may be protective against the myocardial and renal damage induced by a high‐fat diet (HFD). RESULTS Our results showed that CLHs contain large quantities of anserine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The bio-functionalities of CLHs had been proven due to BCAAs, taurine, acidic amino acid, and anserine [ 2 , 3 , 21 , 23 , 30 ]. In this study, the CLHs could decrease ( p < 0.05) body weight gains against the long-term HFD (fat: 46.5 kcal%) induction in mice ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bio-functionalities of CLHs had been proven due to BCAAs, taurine, acidic amino acid, and anserine [ 2 , 3 , 21 , 23 , 30 ]. In this study, the CLHs could decrease ( p < 0.05) body weight gains against the long-term HFD (fat: 46.5 kcal%) induction in mice ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 or 2) were housed in one cage. The AIN-93M formula-based diet was prepared and served, and CLHs were mixed with basal feed ingredients according to our previous study within the 20-week experimental period [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In anesthetized rats, the anserine injection has a dose-dependent effect on increasing blood pressure ( Tanida et al, 2015 ). Nevertheless, an increase in dietary uptake of anserine is thought to be beneficial for preventing and treating obesity and cardiovascular dysfunctions amid other diseases ( Wu et al, 2020 ). Still, more studies are necessary to assess anserine functions during pregnancy and the effects of its reduction in patients with HDP.…”
Section: Discussionmentioning
confidence: 99%
“…cLH was shown to exert a cardioprotective effect by blocking the autophagy pathway at an early stage, which could lead to normal cardiac regulation in mice. This effect is attributed to a combination of its hepatic lipid-lowering effect and systemic antioxidation, mainly associated with the content of different bioactive substances such as anserine, taurine, glutamic acid, aspartic acid, branched chain AAs, α-alanine and histidine, and the presence of antioxidant minerals ( e.g ., Mn, Zn, and Se) in the hydrolysates ( Wu et al, 2020 ).…”
Section: Biological Activities Of Peptides Obtained From Poultry By-p...mentioning
confidence: 99%
“…The most recent research involves oral administration of hydrolyzed cartilage extract in the prevention of osteoarthritis ( Ma et al, 2021 ). Studies have also shown effects in the prevention of cardiovascular diseases ( Wu et al, 2020 ) and chronic liver diseases ( Chen et al, 2017 , Lin et al, 2017 , Wu et al, 2021 ), in antihypertensive treatments ( Bravo et al, 2019 , Mas-Capdevila et al, 2020 ), in the regulation of lipid metabolism as alternative treatments for obesity ( Yang et al, 2014 ) and to obtain antioxidant agents ( Chou et al, 2014 ).…”
Section: Biological Activities Of Peptides Obtained From Poultry By-p...mentioning
confidence: 99%